Kazimiero Kristupo Daukšos žodynas - Subačius, Giedrius (Baltistica, 1992)
THE DICTIONARY OF KAZIMIERAS KRISTUPAS DAUKŠA In Poznan University library a part of K. K. Daukša’s (1796–1865) dictionary was found. This text (1836-1844) contains about 8000 entries, but the whole manuscript could contain about 11000 entries. The dictionary was devoted most probably to young learning people. Phonetic forms throughout this work are based on the East Aukshtaitish dialect; the orthography is very peculiar, the tendency to avoid the Polish one can be seen. The verb is the most significantly presented part of speech in the dictionary. Besides the vocabulary of the living language the manuscript contains many words from K. Sirvydas ’s Dictionarium, the Bible, S. Daukantas’s works. The text of the manuscript suffered a lot of editorial notes made by the author’s son E. J. Daukša. It has appeared that a well known manuscript of K. K. Daukša’s Lithuanian grammar was written not by his hand but by that of his son E. J. Daukša – most probably this is the copy of nowadays unknown original manuscript by K. K. Daukša. An attempt to write the dictionary and the grammar in the East Aukstaitish dialect shows K. K. Daukša’s efforts to standardize this dialect, to create a standard language for Lithuania on the ground of the East Aukshtaitish dialect, although unfortunately this had been hardly possible to put into practice.